Cas9 off-target binding to the promoter of bacterial genes leads to silencing and toxicity. Issue 7 (17th March 2023) - Rostain, William; Grebert, Theophile; Vyhovskyi, Danylo; Pizarro, Paula Thiel; Tshinsele-Van Bellingen, Gatwa; Cui, Lun; Bikard, David
Abstract: Genetic tools derived from the Cas9 RNA-guided nuclease are providing essential capabilities to study and engineer bacteria. While the importance of off-target effects was noted early in Cas9's application to mammalian cells, off-target cleavage by Cas9 in bacterial genomes is easily avoided due to their smaller size. Despite this, several studies have reported experimental setups in which Cas9 expression was toxic, even when using the catalytic dead variant of Cas9 (dCas9). Specifically, dCas9 was shown to be toxic when in complex with guide RNAs sharing specific PAM (protospacer adjacent motif)-proximal sequence motifs. Here, we demonstrate that this toxicity is caused by off-target binding of Cas9 to the promoter of essential genes, with silencing of off-target genes occurring with as little as 4 nt of identity in the PAM-proximal sequence. Screens performed in various strains of Escherichia coli and other enterobacteria show that the nature of toxic guide RNAs changes together with the evolution of sequences at off-target positions. These results highlight the potential for Cas9 to bind to hundreds of off-target positions in bacterial genomes, leading to undesired effects. This phenomenon must be considered in the design and interpretation of CRISPR–Cas experiments in bacteria.